2021
DOI: 10.3390/children8060474
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Design in the Field of Education from the Paradigm of Early Intervention

Abstract: Inclusive education and early intervention go hand in hand in the early educational stages to reach the maximum potential of the student body. The aim of this study was to analyze the inclusive profile of an educational center and assess the effectiveness of an inclusive task (designed for this study) in a group of students of early childhood education. This analytical, prospective, descriptive and longitudinal study was conducted from both qualitative and quantitative approaches. From the qualitative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The final result of this research pointed to the need for training and professional development for teachers regarding students with EBDs. Previous studies have shown similar results, wherein teachers often lack the preparedness and feel not trained to teach students with EBDs [ 37 , 58 , 59 , 60 ]. This underscores the need to prepare teachers for teaching students with EBDs in inclusive settings with typically developing peers.…”
Section: Discussionmentioning
confidence: 54%
“…The final result of this research pointed to the need for training and professional development for teachers regarding students with EBDs. Previous studies have shown similar results, wherein teachers often lack the preparedness and feel not trained to teach students with EBDs [ 37 , 58 , 59 , 60 ]. This underscores the need to prepare teachers for teaching students with EBDs in inclusive settings with typically developing peers.…”
Section: Discussionmentioning
confidence: 54%
“…Functional diversity training and the production of innovative activities are essential to maximize inclusion. In this educational center's children with and without disabilities, using play and emotions as a foundation for creative projects increases learning, awareness, empathy, and inclusion (Benítez-Lugo et al, 2021). Sustainable competence development, as per Kioupi and Voulvoulis (2019), should include not only cognitive factors such as knowledge and understanding of processes, as well as higher order reasoning ability such as reasoning and synthesizing, but also social skills, value systems, and emotions, collectively known as the affective domain.…”
Section: Meso Levelmentioning
confidence: 99%
“…Banyak cara yang dapat dilakukan untuk mengenalkan sains pada anak (Campbell et al, 2019). Akan tetapi, jika yang dihadapi anak dengan kebutuhan yang khusus, mempunyai cara yang khusus juga (Akrim & Harfiani, 2019;Benítez-Lugo et al, 2021). Jika guru pada setting PAUD inklusif cenderung mempunyai keterampilan dan cara mengenalkan sains dasar pada anak berkebutuhan khusus, karena sudah dibekali melalui pendidikan dan pelatihan professional (Gezer & Aksoy, 2019;Yada & Savolainen, 2017), lain halnya dengan orang tua yang mempunyai kemampuan yang variatif (Balli, 2016;Goldman & Burke, 2017;Hirano et al, 2016).…”
Section: Pembahasan Cara Orang Tua Mengenalkan Kegiatan Sainsunclassified